Brain networks underlying mental imagery of auditory and visual information. Issue 9 (6th February 2013) - Zvyagintsev, Mikhail; Clemens, Benjamin; Chechko, Natalya; Mathiak, Krystyna A.; Sack, Alexander T.; Mathiak, Klaus
Abstract Mental imagery is a complex cognitive process that resembles the experience of perceiving an object when this object is not physically present to the senses. It has been shown that, depending on the sensory nature of the object, mental imagery also involves correspondent sensory neural mechanisms. However, it remains unclear which areas of the brain subserve supramodal imagery processes that are independent of the object modality, and which brain areas are involved in modality‐specific imagery processes. Here, we conducted a functional magnetic resonance imaging study to reveal supramodal and modality‐specific networks of mental imagery for auditory and visual information. A common supramodal brain network independent of imagery modality, two separate modality‐specific networks for imagery of auditory and visual information, and a common deactivation network were identified. The supramodal network included brain areas related to attention, memory retrieval, motor preparation and semantic processing, as well as areas considered to be part of the default‐mode network and multisensory integration areas. The modality‐specific networks comprised brain areas involved in processing of respective modality‐specific sensory information. Interestingly, we found that imagery of auditory information led to a relative deactivation within the modality‐specific areas for visual imagery, and vice versa. In addition, mental imagery of both auditory and visual information widely suppressed the activity of primary sensory and motor areas, for example deactivation network. These findings have important implications for understanding the mechanisms that are involved in generation of mental imagery.